Spammer and hacker, two old friends - Hayati, Pedram; Potdar, Vidyasagar (IEEE, 2009)
Spammers are always looking for new ways to bypass filters and spread spam content. Currently, spammers have not only improved their spam methods but have also moved towards exploiting software security vulnerabilities in order to spread their spam content. Spammers use weaknesses inside web applications to inject their spam content into legitimate websites, redirect users to their own campaign, misuse web users resources, and hide their footprints. In this paper, we investigate security vulnerabilities that are exploited by spammers. We explain these security vulnerabilities, list their importance and provide a scenario of how spammers can exploit them. Additionally, we discuss two possible solutions to counter problems by patching and secure software development. The result of our work highlights importance of concerning security best-practices in developing secure software which lack of that would result to demotion of website popularity, blacklisting of website and lose of users' trust.